Sistem Informasi Kas Masuk Dan Kas Keluar Pada Bengkel Las Ragil Karya Semarang - Frisca Tiara Zheninta; Febryantahanuji Febryantahanuji (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2025)
Cash flow management is a crucial aspect of maintaining liquidity and business continuity, particularly for small and medium-sized enterprises (SMEs). However, manual bookkeeping methods that are still widely used often lead to several problems, such as delays in financial reporting, recording errors, and inadequate data security. This article presents a theoretical review of the concepts of information systems, cash inflows and outflows, databases, programming, and data security that are relevant to the development of financial information systems. Based on the literature review, information systems integrated with databases and equipped with security features can improve the efficiency, accuracy, and reliability of financial records. This study emphasizes that the application of technology-based information systems not only supports the preparation of financial statements but also serves as an essential foundation for managerial decision-making and strategic business planning.